Survey of Toilet Sanitary Facilities and Water Hygiene in Rural Communities of Ovia Areas, Edo state, Nigeria - Akingbade, Timothy A.; Aideyan, Osarenmwanta Daniel (NIU Journal of Social Sciences, 2020)
Toilet sanitary facilities and water hygiene are important aspects or rural health. Without proper toilet facilities and water hygiene, human lives can be at serious health risks. The study focused on the survey of toilet sanitary facilities and water hygiene in rural communities of Ovia areas, Edo state. The study employed the cross sectional form of descriptive research design where four research questions were answered. The sample consists of 2 individuals from the 200 households selected from Ovia south west and Ovia North East local government areas of Edo state. Focus group discussion was used among 120 respondents which were selected purposively (60 respondents each from Ovia south west and Ovia North East local government areas). In addition, checklist was also used to elicit data for the study. The checklist and focus group discussion documents were administered by the researchers only except for the questionnaires that were administered with the aid of research assistants. The research instruments were ascertained valid by three experts in the field of health education and environmental health education from the University of Benin and University of Ilorin, Nigeria. A reliability coefficient of 0.69 was obtained through the split half approach of Cronbach alpha analysis. The completed series of instruments were collected, sorted and coded and descriptively analyzed by frequency counts and percentages. The findings of the study revealed that the rural communities of Ovia areas, Edo state uses ventilated improved pit latrine, ordinary pit latrine, water closet and aqua privy with soak away, however, the ordinary pit latrine is the commonest type of toilet facilities use in the rural communities of Ovia areas, Edo state. The toilet facilities in the rural communities, Edo state are majorly dilapidated, unsanitary and poorly sited. The rural communities of Ovia areas, Edo state uses water, tissue, paper, dried leaves and combination of the materials, however water and paper are the commonest type of self-cleaning materials in the rural communities of Ovia areas, Edo state. Majority of community members demonstrate poor water hygiene practice in rural communities of Ovia areas, Edo state. The researchers recommended among others that Local government chairmen and councilors should support community members with water closet to replace the pit latrines as many health hazards are associated with pit latrines. Keywords: Toilet, Sanitary facilities, water hygiene and Rural communities